2011
DOI: 10.1371/journal.pone.0020141
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Biological Surrogates for Predicting Patterns of Marine Biodiversity: A Global Meta-Analysis

Abstract: The use of biological surrogates as proxies for biodiversity patterns is gaining popularity, particularly in marine systems where field surveys can be expensive and species richness high. Yet, uncertainty regarding their applicability remains because of inconsistency of definitions, a lack of standard methods for estimating effectiveness, and variable spatial scales considered. We present a Bayesian meta-analysis of the effectiveness of biological surrogates in marine ecosystems. Surrogate effectiveness was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 50 publications
4
110
1
Order By: Relevance
“…marine environments, whereas others have reported results entirely opposite to ours (namely, lowest congruence at extremes of spatial scale) 8,30 . However, these differences are clearly attributable to methodological considerations: Mellin et al 31 use 4100 km 2 as their highest category of spatial extent, six orders of magnitude lower than our maximum recorded values, whereas Wolters et al 30 use analysis of grain size rather than spatial extent. These are independent metrics that-as we and others have shown-have differing effects on observed patterns of biodiversity 35,50 .…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…marine environments, whereas others have reported results entirely opposite to ours (namely, lowest congruence at extremes of spatial scale) 8,30 . However, these differences are clearly attributable to methodological considerations: Mellin et al 31 use 4100 km 2 as their highest category of spatial extent, six orders of magnitude lower than our maximum recorded values, whereas Wolters et al 30 use analysis of grain size rather than spatial extent. These are independent metrics that-as we and others have shown-have differing effects on observed patterns of biodiversity 35,50 .…”
Section: Discussioncontrasting
confidence: 55%
“…It also suggests a need for caution when synthesizing research on processes that vary across spatial scales. For instance, Mellin et al 31 report linearly decreasing congruence with increasing spatial scale in Full coefficient estimates and their degree of statistical significance are given in Table 2. marine environments, whereas others have reported results entirely opposite to ours (namely, lowest congruence at extremes of spatial scale) 8,30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terlizzi et al (2009) also found that replacing species by genera or families do not cause much information loss in case of betadiversity of mollusks in four marine localities in Norway, Italy, New Zealand and the Arctic. There were, however, some publications which showed that the results obtained from surrogates do not always reflect the ones got from more detailed analyses and can also depend on the statistical method used (Mellin et al 2011). The results of the presently studied material showed that the use of higher taxonomic level (genera and particularly families) does not allow for the recognition similar assemblages in nondisturbed areas as were found on the basis of species study (Figs.…”
Section: From Species To Families-usefulness Of Surrogacy Measuresmentioning
confidence: 70%
“…Whereas previous studies have provided critical insights into spatial structuring of ecosystems, it remains unclear whether heterogeneities manifested within single taxonomic groups reflect b-diversity of communities [14]. Yet the use of a single taxon, or biological surrogate, to estimate biodiversity is becoming increasingly important in marine conservation because of the costs of marine biodiversity surveys, undescribed species, and challenging species identifications [15][16][17]. Although empirical assessments of 'entire communities' are not feasible, it is viable to collect multi-taxic data (multiple phyla) to evaluate the effectiveness of surrogate taxa (e.g.…”
Section: Introductionmentioning
confidence: 99%